Sources of Frustration Among Patients Diagnosed With Renal Cell Carcinoma - Bergerot, Cristiane Decat; Battle, Dena; Bergerot, Paulo Gustavo; Dizman, Nazli; Jonasch, Eric; Hammers, Hans J.; George, Daniel J.; Bex, Axel; Ljungberg, Borje; Pal, Sumanta Kumar; Staehler, Michael D. (Frontiers in Oncology, 2019)
Despite numerous therapeutic advances in renal cell carcinoma (RCC), little is known about patients’ perspectives on cancer care. An international survey was conducted to identify points of frustration associated with cancer care reported by patients with RCC. Data were obtained from an online survey, conducted from April 1 to June 15, 2017, through social media and patient networking platforms. This survey obtained baseline demographic, clinicopathologic, and treatment-related information. Open-ended questions accessed sources of frustration in cancer-related care and patients’ suggestions for amelioration. Responses were categorized and reviewed by independent reviewers. A qualitative analysis was performed and the Kruskal-Wallis test was used to define associations between baseline characteristics and sources of frustration. Among 450 patients surveyed, 71.5% reported sources of frustration, classified as either emotional (48.4%) or practical (23.1%). The most common were fear of recurrence/progression (15.8%), distrust of their cancer care system (12.9%), and lack of appropriate information (9.8%). Female gender and non-clear cell histology were associated with both types of frustration, and older age was linked to practical sources of frustration. Patients suggested solutions included greater compassion among health care practitioners (20.7%), better access to information (15.1%) and research to improve their chances of being cured (14.7%). Sources of frustration related to emotional and practical causes were identified amongst patients with RCC. Certain demographic and clinical characteristics were associated with more sources of frustration. This study provides the first characterization of specific ways to improve the patient experience by addressing common frustrations.